ANALISIS NILAI TOLERANSI PADA MATA PELAJARAN PPKN SEBAGAI UPAYA MENCEGAH TINDAKAN INTOLERANSI DI KELAS IX C SMPN 1 SEMITAU TAHUN PELAJARAN 2022/2023 - Fusnika Fusnika; Agnesia Hartini; Hendrikus Meido Cali (STKIP Persada Khatulistiwa Sintang, 2023)
The problem in research regarding the value of tolerance in Civics subjects as an effort to prevent acts of intolerance in class IX C of SMP Negeri 1 Semitau. The aim of the research is to describe the value of tolerance through PPKn lessons as an effort to prevent acts of intolerance by teachers to form the value of tolerance in students at SMP Negeri 1 Semitau. Data collection through observation, interviews and documentation. The data analysis techniques that the author uses are data presentation, data reduction, and drawing conclusions. Researchers used descriptive qualitative methods. The subjects and objects of research are PPKn subject teachers and students. The results of this research are that the tolerance value of students in Class IX C of SMP Negeri 1 Semitau is still low, namely there is a lack of respect and appreciation between each student and each other. Application of tolerance values to prevent intolerance in PPKn subjects in class IX C of SMP Negeri 1, namely through PPKn lessons. Efforts are being made to foster the value of tolerance to prevent intolerance in Civics subjects in class IX C of SMP Negeri 1, namely getting students to learn to appreciate and respect their classmates and teachers, in order to foster a spirit of tolerance and motivate students to be tolerant of each other. and there needs to be improvement from schools, namely teachers, so that the expected value of tolerance is realized in order to prevent intolerance. .Keywords: Keywords: Tolerance Values, PPKn Subjects, Intolerance.